(Re)Visiting Private Television Research in Bangladesh: Call for New Research Agenda in News Media Study (Social Science Review, 2023)
Private television is the most popular mass media in Bangladesh with a vast audience of both news and programs. However, research on private television and its news media has not advanced sufficiently. Analysing available research on different databases this study identifies general trends in Bangladesh’s private television and its news media research which shows that in addition to low volume of research, most of the study focused on some common aspects resulting in many significant areas unexamined. Finally, this article suggests new agendas in news media research with particular focus on the role of the state, ownership and news labour—three key stakeholders of the private television news media. This investigation will contribute to the scholars and industry insiders to identify the gap in private television research, especially in relation to the news media, and take necessary initiatives.Social Science Review, Vol. 39(2), June 2022 [Special Issue] Page 79-98